Probing yield inefficiencies in Gobhi sarson via frontline demonstrations in heavy soils of South-Eastern part of Punjab - Vipan Kumar Rampal; Reet Verma; Amanpreet Singh (Journal of Oilseed Brassica, 2025)
Rapeseed-mustard is a key oilseed crop in India, contributing significantly to the national economy and edible oil supply. However, conventional rapeseed varieties contain high erucic acid and glucosinolate content, negatively impacting human health and animal feed quality. To address these concerns, canola-quality rapeseed-mustard varieties with low erucic acid (